2021
DOI: 10.1055/a-1487-8625
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphataufnahme durch auf dem deutschen Markt befindliche Alleinfutter und Nierendiäten für Hunde und Katzen

Abstract: Zusammenfassung Gegenstand und Ziel Da die Höhe der Aufnahme an Gesamtphosphor sowie speziell hochlöslichem und damit hochverfügbarem Phosphor mit der Nahrung Effekte auf gesunde und niereninsuffiziente Hunde und Katzen haben kann, wurden auf dem deutschen Markt erhältliche Alleinfuttermittel sowie Alleinfuttermittel für Katzen bzw. Hunde mit chronischer Niereninsuffizienz analysiert. Material und Methoden Bei 133 Alleinfuttermitteln für gesunde Hunde und Katzen (Alleinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Besides, phosphate salts permitted as food and feed additives deliver a cation with the phosphate, in this case sodium. The majority of commercially available processed food products for cats supply major minerals in abundance [33,80,81], which makes the mineral profile of this test diet practically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, phosphate salts permitted as food and feed additives deliver a cation with the phosphate, in this case sodium. The majority of commercially available processed food products for cats supply major minerals in abundance [33,80,81], which makes the mineral profile of this test diet practically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the source of dietary phosphate needs to be considered when formulating diets for CKD patients as well as healthy individuals. Yet, a recent study of Dobenecker (2021) [33] demonstrated that the concentration of phosphate in commercial pet foods, including renal diets, often greatly exceeds the recommended allowance given by the NRC [34] and these diets often contain high percentages of highly water soluble phosphate. A considerable number of products for human consumption are also known to be enriched with inorganic phosphate and are therefore not recommended for kidney patients [26,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic salts of phosphoric acid and phosphorus from bones and cartilage, i.e., ‘organic’ phosphates from carcass meal and bone meal, were given in amounts similar to those used in the study of Dobenecker et al [ 37 ]. Total phosphorus amounts of this magnitude can also be found in pet food products on the market [ 45 ]. Inorganic phosphates are used in processed feed products for technical purposes, including water binding, preservation, texture, colour, and palatability enhancement.…”
Section: Discussionmentioning
confidence: 99%